Sardiyah al-nass al-adabi - Laftah, Diya' Ghani; Laftah, Awwad Kazim ('Amman : Dar al-Hamid, 2011)
Arabic literature; 20th century; narration; rhetoric.
Includes bibliographical references (p. 216-217)
Keywords: Arabic literature -- 20th century -- History and criticism; Narration (Rhetoric); Discourse analysis, Narrative -- Arab countries